2015
DOI: 10.1111/aos.12901
|View full text |Cite
|
Sign up to set email alerts
|

Needle size in intravitreal injections – pain evaluation of a randomized clinical trial

Abstract: ABSTRACT.Purpose: To evaluate the influence of the needle size used for intravitreal (IVT) injections on patients' pain experience in a randomized, double-armed, singleblinded, clinical trial. Methods: Patients included were randomized to have an IVT injection performed with a 27-gauge needle (group 1) or with a 30-gauge needle (group 2). The topical anaesthesia before the injection was standardized. Immediately after the injection, patients were asked to grade their pain using the visual analogue scale (VAS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 32 publications
2
45
2
1
Order By: Relevance
“…Contrary to previous studies, we found that sex was a significant contributor, such that females reported higher pain scores during IVB (p = 0.001) even after adjusted in multivariate regression analysis (Table 3). Similarly, Haas et al [37] reported higher VAS pain scores in females. They suggested that females are more sensitive than males to noxious stimuli and have lower levels of stress-induced analgesia.…”
Section: Discussionmentioning
confidence: 83%
“…Contrary to previous studies, we found that sex was a significant contributor, such that females reported higher pain scores during IVB (p = 0.001) even after adjusted in multivariate regression analysis (Table 3). Similarly, Haas et al [37] reported higher VAS pain scores in females. They suggested that females are more sensitive than males to noxious stimuli and have lower levels of stress-induced analgesia.…”
Section: Discussionmentioning
confidence: 83%
“…These features will facilitate the drug delivery under direct visualization and subsequent noninvasive imaging in vivo. Intravitreal injection is a precise delivery approach which can maximize the drug intensity within eyeball (Haas et al, 2016). After injected into the vitreous humor, the therapeutic agents can touch a substantial fraction of the outer retina, avoiding the side effects on unwanted organs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that needle diameter is correlated to discomfort during the injection process, with comfort levels improving as needle size decreases from 26 to 33 gauge. [34][35][36][37]…”
Section: Other Comfort Measuresmentioning
confidence: 99%